Upaya Hukum Dalam Pencegahan Aksi Lempar Batu Terhadap Pengguna Jalan Raya di Situbondo - Fighur Firmansyah, Moh; Winiari Wahyuningtyas, Yuli; Nofitasari, Solehati; Supianto (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2024)
The recent increase in violent acts is often seen in society,along with various problems related to law violations, from mild toserious. One of the problems is the stone throwing action thatoccurred in Situbondo from 2018 to 2024 there are several cases ofstone throwing in the Situbondo Regency area which have not beencompleted and often occur repeatedly. The Crime of Destruction ofGoods itself has been cited in Article 406 paragraph (1) of theCriminal Code. With 2 problem formulations, namely: 1. What arethe legal remedies of victims of the crime of throwing stones againstmotorists on the Situbondo highway?, What is the legal threat tothe perpetrators of throwing stones against motorists on theSitubondo highway? The research method uses an empiricaljuridical approach, the data used are secondary data and primarydata. The study was carried out by literature studies and fieldstudies. The resource persons in this study are from the SitubondoPolice Gakkum Office. Based on the formulation of the problem andthe discussion in this study, the conclusion of this study is, Legalefforts to protect victims of crime as parties seeking justice, thenthey have the right to legal protection and redress as stated in LawNumber 8 of 1981 concerning the Criminal Procedure Code whichincludes the Road to obtain justice and obtain justice, entitled torestitution, compensation.